Synthesis and properties of perfluoroalkylated TIPS-pentacenes. Issue 47 (22nd November 2019) - Agou, Tomohiro; Suzuki, Seima; Kanno, Yasunori; Hosoya, Takaaki; Fukumoto, Hiroki; Mizuhata, Yoshiyuki; Tokitoh, Norihiro; Suda, Yuki; Furukawa, Shunsuke; Saito, Masaichi; Kubota, Toshio
Abstract: The introduction of perfluoroalkyl (Rf) groups into polycyclic aromatic hydrocarbons (PAHs) is a potential strategy for developing air-stable electron-acceptors that are useful for manufacturing novel n-type organic semiconductors. This paper describes a facile synthetic method for 9, 13-bis[(triisopropylsilyl)ethynyl]pentacene ("TIPS-pentacene") derivatives bearing two or four Rf groups at peripheral regions. The molecular structures of newly synthesized TIPS pentacenes bearing four Rf groups were established by single-crystal X-ray analysis. The Rf-substituted TIPS-pentacenes are stable both in solutions and in the solid state under ambient conditions, probably because of the combination of the TIPS-ethynyl and Rf groups. The Rf groups stabilize the π-orbitals of the TIPS-pentacene framework and improve the electron-accepting properties, as evidenced by electrochemical measurements and photoelectron yield spectroscopy (PYS). Graphical abstract: Image 1 Highlights: TIPS-pentacenes bearing two or four perfluoroalkyl (Rf) groups were synthesized. The molecular structures of the Rf-substituted TIPS-pentacenes were established by the single crystal X-ray diffraction measurements. The Rf-substituted TIPS-pentacenes exhibited good thermal- and photo-stability under ambient conditions. Electron-withdrawing Rf groups stabilized the π-orbitals of the Rf-substituted pentacenes.